2014
DOI: 10.1021/bm401431t
|View full text |Cite
|
Sign up to set email alerts
|

Solution-State Polymer Assemblies Influence BCS Class II Drug Dissolution and Supersaturation Maintenance

Abstract: Spray dried dispersions (SDDs), solid dispersions of polymer excipients and active pharmaceuticals, are important to the field of oral drug delivery for improving active stability, bioavailability, and efficacy. Herein, we examine the influence of solution-state polymer assemblies on amorphous spray-dried dispersion (SDD) performance with two BCS II model drugs, phenytoin and probucol. These drugs were spray dried with 4 model polymer excipients consisting of poly(ethylene-alt-propylene) (PEP), N,N,-dimethylac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 58 publications
1
62
0
Order By: Relevance
“…Drug nucleation and crystal growth may be influenced by the intermolecular interactions between PPI and drug molecules in the bulk solution . For example, the effectiveness of PPIs in inhibiting the formation of carbamazepine dihydrate was related to the intermolecular hydrogen bonding and hydrophobic interactions between PPIs and carbamazepine but their relative impact on the effectiveness of a given PPI could not be determined because of the experimental limitations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug nucleation and crystal growth may be influenced by the intermolecular interactions between PPI and drug molecules in the bulk solution . For example, the effectiveness of PPIs in inhibiting the formation of carbamazepine dihydrate was related to the intermolecular hydrogen bonding and hydrophobic interactions between PPIs and carbamazepine but their relative impact on the effectiveness of a given PPI could not be determined because of the experimental limitations .…”
Section: Introductionmentioning
confidence: 99%
“…Drug nucleation and crystal growth may be influenced by the intermolecular interactions between PPI and drug molecules in the bulk solution. [11][12][13][14] For example, the effectiveness of PPIs in inhibiting the formation of carbamazepine dihydrate was related to the intermolecular hydrogen bonding and hydrophobic interactions between PPIs and carbamazepine but their relative impact on the effectiveness of a given PPI could not be determined because of the experimental limitations. 11 In another study, the superiority of HPMC-AS HF over HPMC-AS LF, two different grades of HPMC-AS containing different ratios of acetate and succinate substituents, in inhibiting the precipitation of carbamazepine from an aqueous solution was attributed to stronger hydrophobic interactions between HPMC-AS HF and carbamazepine in the bulk solution.…”
Section: Introductionmentioning
confidence: 99%
“…1619 In our studies, subtle molecular attributes that influence supersaturation such as amphiphilicity, ionic character, and related chemical properties have been identified. However, these functionalities are unable to maintain high supersaturation of drugs with fast recrystallization kinetics.…”
mentioning
confidence: 98%
“…Similar results showed that HPMCAS systems performed better than or at least comparably to PVPVA systems, regardless of the drug loading or dose (23). Additionally, site-specific delivery could be obtained using enteric polymer HPMCAS or Eudragit L 100-55 (63,64).…”
Section: (1) Formulation Aspectsmentioning
confidence: 99%
“…Solid-state structures of spray-dried dispersions showed a single-glass transition of a homogeneous mixture of drug/polymer. Forced aggregation of the polymer into regular micelle structures was found to be a critical factor in increasing the dissolution rate and supersaturation maintenance of spray-dried SDs (63). Lyophilization is an alternative to develop rapid-dissolving formulations (73).…”
Section: (1) Formulation Aspectsmentioning
confidence: 99%